Prioritization of watershed management scenarios under climate change in the Jemma sub-basin of the Upper Blue Nile Basin, Ethiopia - Gebrekidan Worku (Journal of Hydrology: Regional Studies, 2020)
Study region: Jemma sub-basin, Upper Blue Nile Basin, Ethiopia. Study focus: This study develops watershed management alternatives which can ensure optimal climate change adaptation benefits under different climate scenarios. The climate scenarios were developed using the statistically bias corrected, multi-model ensemble mean and the RCP 4.5 and RCP 8.5 emission scenarios. The hydrological impact of climate change was assessed using a multi-gauge calibrated and validated the Soil and Water Assessment Tool (SWAT) model. Watershed management alternatives were prioritized using a multi-criteria decision analysis which intercompared watershed management criteria and alternatives through the Analytic Hierarchy Process. New hydrological insights: The findings showed a consistent decline of rainfall, surface runoff and total water yield under all climate scenarios and climate impact scenarios. Water harvesting structures were the most prioritized watershed management alternatives to reduce climate change impacts. More than half of the watersheds of the Jemma sub-basin are highly and optimally suitable for in-situ water harvesting under baseline and future climate scenarios. Observed terrace and anticipated in-situ water harvesting structures significantly (p < 0.05) reduced surface runoff and thereby significantly increase soil water under baseline and future climate scenarios. However, both in-situ and ex-situ water harvesting structures caused an insignificant change in the total water yield under climate scenarios. We conclude implementing in-situ water harvesting structures can help to increase green water without a decline in blue water.